Analysis of Learning Difficulties in Multiplication Operations in Grade 3 Elementary School Based on the SOLO Taxonomy - Sartika, Rika; Anjarini, Titi; Suyoto, Suyoto (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2025)
This study aims to analyze the learning difficulties experienced by third-grade elementary school students in solving multiplication problems based on the Structure of the Observed Learning Outcome taxonomy. The research employed a descriptive qualitative approach involving thirty students as participants. Data were collected through written tests, observation, and interviews to identify the level of understanding and the types of difficulties encountered. The analysis technique categorized student responses into conceptual levels, namely prestructural, unistructural, multistructural, relational, and extended abstract. The results showed that the students’ average score of 2.77 out of five indicated a moderate ability level. Approximately 36.7 percent of students answered three questions correctly, while only 6.7 percent answered all correctly. Most students were found at the multistructural to relational levels, reflecting partial conceptual understanding, while only a few reached the extended abstract level, showing complete integration of ideas. These findings reveal that students still face challenges in connecting conceptual and procedural knowledge in multiplication. The study concludes that the development of conceptual thinking in multiplication occurs gradually, emphasizing the importance of learning strategies that foster integration among concepts and structured problem-solving to enhance students’ mathematical reasoning